Analisa Tebal Perkerasan Kaku pada Ruas Jalan Kalipare Donomulyo STA 0+000-1+000 Kabupaten Malang - Bela, Alfianus Indra ; Kristafi A, Andy; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Road Kalipare-Donomulyo is the access road to the tourist district of Blitar District and also towards the tourist Paths. current road conditions and drainage Kalipare ? Donomulyo much damage because it takes research to identify the damage, plan thick roughness and dimensional proper drainage channels, efficient, as well as optimal in order to working properly. this research aims to know the road repair plan by using the method of NAASRA and drainage improvement plan by using the LOG Method PERSON III. Results in getting from the thick rigid roughness perhitingan Highway Kalipare-Donomulyo STA 0 + 000-1 000 + by using the method of NAASRA, in the rigid kind of roughness can be used is Concrete reinforced with thick layers melted away roughness And 18 cm. The results obtained from the perhitingan on drainage method using LOG PERSON III, i.e. the width of the channel is 0.55 m, channel height of 0.275 m